Multibit racetrack memory - DEĞER, CANER (IOP PUBLISHING LTD, 2020)
We present a hybrid usage of domain walls and skyrmions in the same racetrack memory which can enable developing a platform for many-valued magnetic data storage technology, by numerically solving the Landau-Lifshitz-Gilbert equation. The conversion of domain-walls to magnetic skyrmions in a plain nanotrack without geometrical restrictions allowed us to realize a ternary racetrack memory. Annihilation, conversion, and passing over of the reverse domains are considered as the three-state of ternary logic. We anticipate that multibit racetrack memory will influence the development of data storage platforms for emergent computing technologies.
Keywords: racetrack memory; chiral spin textures; spin currents; micromagnetic simulations; SKYRMIONS